Efektivitas Pembelajaran Pendidikan Agama Islam (PAI) Dalam Membentuk Akhlak Mulia Pada Siswa: Studi Kasus di SMP PAB 15 Medan - Nasution, Alpi Robiah Al Adwiyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Islamic Religious Education (PAI) has an important role in shaping students' noble character and morals, especially at the junior secondary education level. This study focuses on SMP PAB 15 Medan as a case to explore the extent of the effectiveness of PAI learning in forming noble morals in students. This type of research uses qualitative research, using a case study research approach which is taken in the form of case study research that occurs and is incentive in nature, detailed and in-depth regarding an educational institution. This research aims to collect the information needed to see the existing conditions regarding the Effectiveness of Islamic Religious Education (PAI) Learning. The results of this research are in Forming Noble Morals in Students: Case Study at Smp Pab 15 Medan. Effective Islamic Religious Education (PAI) learning involves various comprehensive and student-centered approaches.